Hepatitis B seroprotection in children aged 10-15 years after completion of basic hepatitis B immunizations - Novie Homenta Rampengan; Sri Rezeki Hadinegoro; Mulya Rahma Karyanti (Indonesian Pediatric Society, 2017)
Background The prevalence of hepatitis B viral (HBV) infection in Indonesia is high. The most effective way to control HBV infection is by hepatitis B (HB) immunization. Many studies reported that hepatitis B surface antibody (anti-HBs) seroprotection declines in children > 10 years of age. In addition many factors can influence anti-HBs titer.Objective To measure anti-HBs titer and evaluate possible factors associated with anti-HBs titer.Methods This cross sectional study was conducted in children 10-15 years of age from ten schools at Tuminting District, Manado, North Sulawesi, from October to November 2014. All subjects had completed the hepatitis B immunization scheme. By stratified random sampling, 105 children were selected as subjects. Data was analyzed with SPSS version 22.Results. From 48 schools, we selected 10 schools from which to draw a total of 105 children, but only 23 (21.9%) children had detectable anti-HBs . Of all subjects, 76 (72.4%) were female, 78 (74.3%) had good nutritional status, and 98 (93.3%) had birth weight ≥2,500 grams. Data from immunization record books showed that 26 (24.8%) subjects received the HB-1 vaccination at ≤7 days of age and 45 (42.9%) subjects had a ≥2 month interval between the HB-2 and HB-3 vaccinations. Multivariate analysis showed that administration of HB-1 at ≤7 days of age and a ≥2 month interval between HB-2 and HB-3 had significant associations with anti-HB seroprotection in children.Conclusion A low proportion of subjects who had completed the hepatitis B immunization scheme had detectable anti-HBs titer (21.9%). Administration of HB-1 at ≤7 days of age and a ≥2-month interval between HB-2 and HB-3 vaccinations are important factors in anti-HB seroprotection in children aged 10-15 years.